Translating indigenous knowledges towards a sensuous translation - Vidal Claramonte, Mª Carmen Àfrica 1964- (Routledge, Taylor & Francis Group, 2025)
"In this book, Vidal presents a new way of translating indigenous epistemologies. For centuries, the Western world has ordained what knowledge is, what it should be and has also been responsible for transmitting that knowledge. This 'universal' knowledge has traveled to the four corners of the globe. In recent decades, there has been a steadily growing interest in dialogical epistemologies. Disciplines ranging from historiography and philosophy to anthropology are calling for this universalist idea of knowledge to be modified. Thanks to this change of perspective, other forms of knowledge, which until now have been ignored, are gradually coming to light. Indigenous knowledges are not constructed with the scientific, binary, static, Cartesian, univocal logic characteristic of Western societies. Non-Western types of knowledge incorporate senses, emotions, body, objects, and matter. It is impossible to reduce indigenous knowledges to Western conceptualizations."
Keywords: Indigenes Volk; Lokales Wissen; Übersetzung; Geistesleben; Lateinamerika; Translating and interpreting; Knowledge, Theory of; Indigenous peoples / Intellectual life; Théorie de la connaissance; epistemology